2014
DOI: 10.1111/hepr.12417
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil/lymphocyte ratio as a prognostic indicator of hepatic arterial infusion chemotherapy with arterial cisplatin plus continuous 5‐fluorouracil

Abstract: HAIC is a candidate for treatment of advanced HCC, and NLR may be a useful prognostic indicator for suitability of HAIC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Inflammation-related markers, such as the absolute leukocyte count, C-reactive protein level, neutrophil to lymphocyte ratio (NLR), and cytokine level, have been linked to clinical outcomes in patients with various malignancies, including HCC [34]. In a study by Tajiri et al [35], NLRs of 4 or more (odds ratio, 0.49; p=0.04) correlated with low RRs, whereas NLRs less than 4 correlated with prolonged OS, as did treatment response. In a study by Terashima et al [36], patients with high NLRs (cut-off value=2.87) had significantly shorter MSTs (5.6 and 20.7 months, respectively; p<0.01) and significantly worse RRs (21.1% and 37.7%, respectively; p<0.01) than patients with low NLRs.…”
Section: Predictive Factors For Response and Survivalmentioning
confidence: 99%
“…Inflammation-related markers, such as the absolute leukocyte count, C-reactive protein level, neutrophil to lymphocyte ratio (NLR), and cytokine level, have been linked to clinical outcomes in patients with various malignancies, including HCC [34]. In a study by Tajiri et al [35], NLRs of 4 or more (odds ratio, 0.49; p=0.04) correlated with low RRs, whereas NLRs less than 4 correlated with prolonged OS, as did treatment response. In a study by Terashima et al [36], patients with high NLRs (cut-off value=2.87) had significantly shorter MSTs (5.6 and 20.7 months, respectively; p<0.01) and significantly worse RRs (21.1% and 37.7%, respectively; p<0.01) than patients with low NLRs.…”
Section: Predictive Factors For Response and Survivalmentioning
confidence: 99%
“…The Glasgow Prognostic Score (GPS), which combines serum CRP with albuminemia and has been demonstrated to be a predictive factor in various cancers, is regarded as a prognostic milestone among all the systems (Forrest, McMillan, & McArdle, ; McMillan, ). Other prognostic systems such as neutrophil to lymphocyte ratio (NLR) (Cho et al, ; McNamara et al, ; Tajiri et al, ), platelet to lymphocyte ratio (PLR) (Kwon, Kim, & Oh, ; Li et al, ), and fibrinogen (He et al, ; Luo, Kim, Kim, Lee, & Song, ; Seebacher et al, ), can help predict the progression, metastasis, and prognosis of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Terashima et al found that in 266 patients undergoing hepatic arterial infusion chemotherapy, elevated NLR was associated with a significantly worse response rate (55). Similar findings were revealed by Tajiri et al in 26 patients in which patients with elevated NLR were half as likely to respond to hepatic arterial infusion chemotherapy (56). Finally, elevated NLR in patients receiving selective internal radiation therapy (57) and those who underwent resection for tumors at least 10 cm in size (58) had significantly worse outcomes if NLR was elevated.…”
Section: Neutrophil Lymphocyte Ratio (Nlr)mentioning
confidence: 60%